2014
DOI: 10.1186/1471-2407-14-172
|View full text |Cite
|
Sign up to set email alerts
|

Metformin enhances tamoxifen-mediated tumor growth inhibition in ER-positive breast carcinoma

Abstract: BackgroundTamoxifen, an endocrine therapy drug used to treat breast cancer, is designed to interrupt estrogen signaling by blocking the estrogen receptor (ER). However, many ER-positive patients are low reactive or resistant to tamoxifen. Metformin is a widely used anti-diabetic drug with noteworthy anti-cancer effects. We investigated whether metformin has the additive effects with tamoxifen in ER-positive breast cancer therapy.MethodsThe efficacy of metformin alone and in combination with tamoxifen against E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 32 publications
4
45
0
Order By: Relevance
“…Similar to CYP3A4 silencing (Mitra et al, 2011), metformin was also found to inhibit Stat3 signaling in breast cancer (Deng et al, 2012), suggesting that metformin might inhibit CYP3A4 mediated EET biosynthesis. Metformin inhibits mammary tumor growth (Iliopoulos et al, 2011; Ma et al, 2014), suppresses mitochondrial respiration (Wheaton et al, 2014) and can be modified easily by click chemistry using the cyano-guanidine condensation reaction (Choi et al, 2016; Kim et al, 2012b; Row et al, 2016). Nonetheless, metformin lacks potency, particularly in ER+HER2− breast cancer (Ma et al, 2014), and potency can’t yet be improved by structure activity studies, because a structural target for metformin remains to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to CYP3A4 silencing (Mitra et al, 2011), metformin was also found to inhibit Stat3 signaling in breast cancer (Deng et al, 2012), suggesting that metformin might inhibit CYP3A4 mediated EET biosynthesis. Metformin inhibits mammary tumor growth (Iliopoulos et al, 2011; Ma et al, 2014), suppresses mitochondrial respiration (Wheaton et al, 2014) and can be modified easily by click chemistry using the cyano-guanidine condensation reaction (Choi et al, 2016; Kim et al, 2012b; Row et al, 2016). Nonetheless, metformin lacks potency, particularly in ER+HER2− breast cancer (Ma et al, 2014), and potency can’t yet be improved by structure activity studies, because a structural target for metformin remains to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…30 Cells were seeded into 6-well plates (1£10 3 cells per well) and treated with metformin at various concentrations (0 mM, 0.625 mM, 2.5 mM, or 10 mM). After 14 days, the resulting colonies were fixed with 4% cold paraformaldehyde for 15 min and stained with crystal violet (Beyotime C0121) for 15 min at room temperature.…”
Section: Colony Formation Assaymentioning
confidence: 99%
“…Traditionally, patients with type 2 diabetes mellitus and cardiovascular diseases are treated with aspirin and metformin (1)(2)(3). In recent years, both drugs have been reported to decrease the risk of several types of cancers, including breast cancer (4)(5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%